Clinical manifestations of Rift Valley fever in humans: Systematic review and meta-analysis. - Zacchaeus Anywaine; Swaib Abubaker Lule; Christian Hansen; George Warimwe; Alison Elliott (Public Library of Science (PLoS), 2022)
Background Rift Valley fever (RVF) is an emerging, neglected, mosquito-borne viral zoonosis associated with significant morbidity, mortality and expanding geographical scope. The clinical signs and symptoms in humans are non-specific and case definitions vary. We reviewed and analysed the clinical manifestations of RVF in humans. Methods In this systematic review and meta-analysis we searched on different dates, the Embase (from 1947 to 13th October 2019), Medline (1946 to 14th October 2019), Global Health (1910 to 15th October 2019), and Web of Science (1970 to 15th October 2019) databases. Studies published in English, reporting frequency of symptoms in humans, and laboratory confirmed RVF were included. Animal studies, studies among asymptomatic volunteers, and single case reports for which a proportion could not be estimated, were excluded. Quality assessment was done using a modified Hoy and Brooks et al tool, data was extracted, and pooled frequency estimates calculated using random effects meta-analysis. Results Of the 3765 articles retrieved, less than 1% (32 articles) were included in the systematic review and meta-analysis. Nine RVF clinical syndromes were reported including the general febrile, renal, gastrointestinal, hepatic, haemorrhagic, visual, neurological, cardio-pulmonary, and obstetric syndromes. The most common clinical manifestations included fever (81%; 95% Confidence Interval (CI) 69-91; [26 studies, 1286 patients]), renal failure (41%; 23-59; [4, 327]), nausea (38%; 12-67; [6, 325]), jaundice (26%; 16-36; [15, 393]), haemorrhagic disease (26%; 17-36; [16, 277]), partial blindness (24%; 7-45; [11, 225]), encephalitis (21%; 11-33; [4, 327]), cough (4%; 0-17; [4, 11]), and miscarriage (54%) respectively. Death occurred in 21% (95% CI 14-29; [16 studies, 328 patients]) of cases, most of whom were hospitalised. Discussion This study delineates the complex symptomatology of human RVF disease into syndromes. This approach is likely to improve case definitions and detection rates, impact outbreak control, increase public awareness about RVF, and subsequently inform 'one-health' policies. This study provides a pooled estimate of the proportion of RVF clinical manifestations alongside a narrative description of clinical syndromes. However, most studies reviewed were case series with small sample sizes and enrolled mostly in-patients and out-patients, and captured symptoms either sparsely or using broad category terms.